Productive parameters of G guinea pigs in the central coast of Peru - Yamada A., Graciela (2018)
The objective of this study was to determine the productive parameters of guinea pigs of the G lineage at the level of the central coast of Peru. Information on productive data was collected from 180 parturitions of 39 breeding guinea pigs and 452 weaned individuals at 16.3 days between April 2016 and May 2017 from the Huaral experimental station of the IVITA Research Centre of the National University of San Marcos. The number of births (NN), number of live births (NNV), body weight at birth (PCrN), litter weight at birth (PCN), number of weaned animals (ND), body weight at weaning (PcrD), litter weight at weaning (PCD) and mortality rate (M). The results were: NN 2.82 ± 1.14 pups per parturition (1-5 pups), NNV 2.80 ± 1.13 pups, PCrN 139.3 ± 30.9 g, PCN 389.6 ± 121.3 g, ND 2.58 ± 1.02 pups, PCrD 248.0 ± 62.3 g, PCD 640.6 ± 211.9 g and M 8.89%. Only PCrD showed significant difference due to the number of parturitions (p<0.05).